Uma Abordagem Determinística e Estocástica na Mensuração das Provisões para Sinistros - Santos, Maysa Pereira de Souza (2021)
Project Work presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Information Analysis and Management